Explorations in English historical syntax - Cuyckens, H.; De Smet, Hendrik; Heyvaert, Liesbet, 1972-; Maekelberghe, Charlotte (Studies in language companion series (SLCS),, 2018)
"The papers in this volume cover a wide range of interrelated syntactic phenomena, from the history of core arguments, to complements and non-finite clauses, elements in the clause periphery, as well as elements with potential scope over complete sentences and even larger discourse chunks. In one way or another, however, they all testify to an increasing awareness that even some of the most central phenomena of syntax - and the way they develop over time - are best understood by taking into account their communicative functions and the way they are processed and represented by speakers' cognitive apparatus. In doing so, they show that historical syntax, and historical linguistics in general, is witnessing a convergence between formerly distinct linguistic frameworks and traditions. With this fusion of traditions, the trend is undeniably towards a richer and more broadly informed understanding of syntactic change and the history of English. This volume will be of great interest to scholars of (English) historical syntax and historical linguistic within the cognitive-linguistic as well as the generative tradition"--